Reducing severance costs or subsidizing permanent job creation: Which policy is more effective to reduce duality? - Victoria Osuna (Economics: The Open-Access, Open-Assessment E-Journal, 2015)
This paper introduces endogenous on-the-job training in the job creation and destruction model of the search and matching type by García-Pérez and Osuna (Dual labour markets and the tenure distribution: Reducing severance pay or introducing a single contract, 2014). The objective is to compare the effects of subsidizing permanent job creation with that of reducing the severance cost gap between permanent contracts (PCs) and temporary contracts (TCs) as a strategy to reduce labour market duality between PCs and TCs. The 2006 and 2012 Spanish labour market reforms are used as a benchmark. The results point to fact that subsidizing permanent job creation may not be the best option from a fiscal point of view to reduce labour market segmentation between PCs and TCs. In particular, the results of introducing the subsidized "entrepreneurs' permanent contract" (EPC) in the 2012 labour market reform may have involved substantial deadweight effects. In fact, the reduction of the severance cost gap to a number close to 15 days of wages per year of service (p.y.o.s.) may generate the same effects, provided dismissals for objective reasons are effectively made easier to justify and firms make use of that option instead of agreeing to an indemnity closer to the amount paid for unfair dismissals. Finally, the model also shows the relevance of designing appropriate penalties for those firms that do not comply with the obligations that subsidies involve.
Keywords: J23; J32; J63; J64; J65; J68; 330; subsidies; severance costs gap; permanent and temporary contracts; duality; unemployment; tenure distribution; job destruction